Psychology : the hope of a science - Kimble, Gregory A. (Bradford book., 1996)
At a time in the history of psychology when many psychologists are troubled by the splintered condition of the field, Gregory Kimble proposes that the diverse perspectives in psychology share ways of thinking that can bring coherence to the discipline. Drawing on years of extensive research and scholarship, Kimble presents evidence for this potential unity. He portrays psychology as a natural science with relevance to human life and offers a set of axioms that hold the field together. Psychology is a two-part exploration of the concept of psychology as the science of behavior. The first part describes the traditional commitments of the scientific method and spells out the implications of those commitments for psychology. The second part develops a general theory within a framework that can be called functional behaviorism, which combines the imperative that a science of psychology must be about observable realities with the view that human behavior is the result of evolution. Kimble's proposals are of general significance and have stood the test of time: they were reasonably explicit in the writings of the giants in the history of psychology, and they apply in contexts that range from behavioral neurology to social action.